2018
DOI: 10.1590/1678-4324-2017160394
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Chromium-Resistance and Uptake by Fungi: Isolated from Industrial Wastewater

Abstract: Trichosporon asahii and Rhodotorula mucilaginosa isolated from wastewater effluents were identified as chromiumresistant yeasts. Cr(VI) concentrations at 8 mM and 6 mM were inhibitory for R. mucilaginosa and T. asahii. Remarkably elevated GSH (69.88 ± 10.01) and GSSG (11.24 ± 0.96) was observed under metal stress in T. asahii as compared to R. mucilaginosa GSH (18.95 ± 3.19) and GSSG (3.7 ± 2.74) mM g-1 8 level. Statistical analysis revealed significantly higher GSH/GSSG ratio in both strains. NPSH (29.84 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…These results also agree with previous reports [25,43,45]. Elahi and Rehman [44] reported that activity of chromate reductase from both T. asahii and R. mucilaginosa was increased in the presence of Na, Ca, Mg, and Co but significantly decreased in the presence of Hg cations.…”
Section: Chromate Reductase Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…These results also agree with previous reports [25,43,45]. Elahi and Rehman [44] reported that activity of chromate reductase from both T. asahii and R. mucilaginosa was increased in the presence of Na, Ca, Mg, and Co but significantly decreased in the presence of Hg cations.…”
Section: Chromate Reductase Characteristicssupporting
confidence: 93%
“…Among bacterial chromate reductases, the optimal temperature varies in the range of 30-50°C [25,42,43]. Elahi and Rehman [44] reported that optimum chromate reductase activity was achieved at pH 6 (50°C) in Trichosporon asahii while Rhodotorula mucilaginosa showed maximum activity at pH 7 (30°C).…”
Section: Chromate Reductase Characteristicsmentioning
confidence: 99%
“…Efficient Cr 6+ biosorption ability was observed in a wide range of fungi groups, i.e., Rhizomucorarrhizu, Aspergillus oryzae, Aspergillus carbonarius, A. niger, Candida tropicalis, Trichoderma sp., Penicillium chrysogenum, and Fusarium oxysporum (Al-Asheh and Duvnjak 1995; Volesky and Holan 1995;Igwe and Abia 2006;Srivastava and Thakur Fig. 3 Growth of Vigna radiata (mung beans) in microbial treated wastewater (with M. testaceum B-HS2), tap water, and untreated wastewater after 10 days of incubation under 1:1 light and dark period indicating that microbially treated wastewater is safe for plant growth (Elahi et al 2019) 2006; Vankar and Bajpai 2007;Ye et al 2010;Amatussalam et al 2011;Rehman and Anjum 2011;Elahi and Rehman 2017).…”
Section: Bioremediation Through Fungimentioning
confidence: 99%
“…Furthermore, they produce various metabolites which also influence metal uptake such as nitrogen-containing ligands, phosphate, and proteins (Bai et al 2012;Chen et al 2012). Elahi and Rehman (2017) reported that Rhodotorula mucilaginosa showed a 0.5-fold increase, whereas Trichosporon asahii exhibited a 0.35-fold increase in chromate reductase activity when compared to the controls. Das and Chandra (1990) working with Cr 6+ Streptomyces sp.…”
Section: Bioremediation Through Fungimentioning
confidence: 99%
“…Fungi and yeast species are also valuable sources for production of ChrR enzymes [34][35][36] . A filamentous fungus, Penicillium sp.…”
Section: Chrrs From Microbial Sourcesmentioning
confidence: 99%